Asymmetric hydroarylation of vinyl ethers catalyzed by a hydroxoiridium complex: azoles as effective directing groups. Issue 18 (17th February 2017) - Yamauchi, Daisuke; Nishimura, Takahiro; Yorimitsu, Hideki
Abstract : Asymmetric hydroarylation of vinyl ethers using azoles as directing groups was realized by use of a hydroxoiridium/chiral phosphine catalyst. Abstract : Catalytic asymmetric hydroarylation of vinyl ethers using 2-aryl-substituted azoles containing an N–H bond as directing groups was realized by use of a hydroxoiridium/chiral phosphine catalyst. The reaction proceeded via C–H activation of the aromatic ring to give high yields of the corresponding addition products with high branch- and enantioselectivity.